2004
DOI: 10.1023/b:plso.0000047767.62179.25
|View full text |Cite
|
Sign up to set email alerts
|

Legume rotation effects on early growth and rhizosphere microbiology of sorghum in West African soils

Abstract: Cereal yield increases in legume rotations on west African soils were the subject of much recent research aiming at the development of more productive cropping systems for the mainly subsistence-oriented agriculture in this region. However, little has been done to elucidate the possible contribution of soil microbiological factors to these rotation effects. Therefore a pot trial was conducted using legume rotation and continuous cereal soils each from one site in Burkina Faso and two sites in Togo where croppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…As observed by other studies, cowpea increased nematode infestation [14], while groundnut decreased the population of nematodes [3,15,16]. The biological effects of legumes are complex [17] but our results showed that the N-effect seemed to be the most important factor governing sorghum response to crop rotation. Nitrogen and P are known to be the most limiting factors of Alfisols and Ultisols of West Africa [1,5].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…As observed by other studies, cowpea increased nematode infestation [14], while groundnut decreased the population of nematodes [3,15,16]. The biological effects of legumes are complex [17] but our results showed that the N-effect seemed to be the most important factor governing sorghum response to crop rotation. Nitrogen and P are known to be the most limiting factors of Alfisols and Ultisols of West Africa [1,5].…”
Section: Discussionsupporting
confidence: 64%
“…The quantity and quality (organic N) supplied by the residues of legumes improve soil N, biological properties and availability of other nutrients, leading to better growth and good health for the succeeding sorghum. As reported inprevious work, subsequent cereal yields are usually increased in legume-cereal rotations [3,4,18] as a consequence of mineral N provided by mineralization of legume residues [19][20][21][22] and the improvement of soil biological properties and availability of nutrients [17]. Then, despite the increase of the population of nematodes, the succeeding sorghum benefits from good nutriational conditions and has quicker and better growth, particularly during the first period of the season.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…P availability had no effect on microbial community composition in the rhizosphere of, for example, Sorghum bicolor (Marschner et al ., 2004b).…”
Section: Rhizosphere Microorganisms and Nutrient Availabilitymentioning
confidence: 99%
“…Other soil chemical properties, such as pH, may also be favourably affected by the cultivation of legumes (Alvey et al 2001;Sanginga 2003;Tian ?tul?> et al 2005). Rotations may affect soil microbial populations, arbuscular mycorrhizae and parasitic nematode populations (Bagayoko et al 2000;Alvey et al 2001Alvey et al , 2003Marschner et al 2004). However, it remains difficult to quantify to what extent changes in soil biota relate to variations in cereal yield.…”
Section: Introductionmentioning
confidence: 99%